2018
DOI: 10.1007/s10461-018-2098-1
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Depressive Symptoms with Lapses in Antiretroviral Medication Adherence Among People Living with HIV: A Test of an Indirect Pathway

Abstract: Viral suppression, a critical component of HIV care, is more likely when individuals initiate antiretroviral therapy (ART) early in disease progression and maintain optimal levels of adherence to ART regimens. Although several studies have documented the negative association of depressive symptoms with ART adherence, less is known about how depressed mood relates to intentional versus unintentional lapses in adherence as well as the mechanisms underlying this association. The purpose of the current study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
0
2
Order By: Relevance
“…We did not find support for the cognitive attributes of adherence self-efficacy and adherence motivation as explanatory mediators in the relationship between depressive symptoms and ART adherence in this population of recently incarcerated PLHIV. Previous studies have found support for adherence self-efficacy as a mediator of this relationship in clinical populations in the U.S. [19,61], and Uganda [18]. While we did find that greater depressive symptoms were associated with lower adherence self-efficacy in this population, greater adherence self-efficacy was not associated with higher ART adherence.…”
Section: Unsupported Mediation Hypothesescontrasting
confidence: 79%
“…We did not find support for the cognitive attributes of adherence self-efficacy and adherence motivation as explanatory mediators in the relationship between depressive symptoms and ART adherence in this population of recently incarcerated PLHIV. Previous studies have found support for adherence self-efficacy as a mediator of this relationship in clinical populations in the U.S. [19,61], and Uganda [18]. While we did find that greater depressive symptoms were associated with lower adherence self-efficacy in this population, greater adherence self-efficacy was not associated with higher ART adherence.…”
Section: Unsupported Mediation Hypothesescontrasting
confidence: 79%
“…A systematic review of 52 studies on the impact of depression on ART adherence found inconsistent results, with 30 studies indicating a direct negative effect of depression on adherence and 22 studies finding no conclusive effect [71]. More recent studies have also reported that depression was not directly associated with ART adherence [46,72]. Our initial model also revealed our data was not compatible with an association between HIV-related stigma and severity of drug dependence or between social support and anxiety.…”
Section: Discussioncontrasting
confidence: 63%